2013
DOI: 10.18632/oncotarget.1581
|View full text |Cite
|
Sign up to set email alerts
|

FAM83D promotes cell proliferation and motility by downregulating tumor suppressor gene FBXW7

Abstract: Amplification of chromosome 20q is frequently found in various types of human cancers, including breast cancer. The list of candidate oncogenes in 20q has expanded over the past decade. Here, we investigate whether FAM83D (family with sequence similarity 83, member D) on chromosome 20q plays any role in breast cancer development. The expression level of FAM83D is significantly elevated in breast cancer cell lines and primary human breast cancers. High expression levels of FAM83D are significantly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 41 publications
(38 reference statements)
6
84
1
1
Order By: Relevance
“…For example NAC has been shown to inhibit mammalian target of rapamycin (mTOR; [59]), possibly by decreasing ROS and consequently inhibiting the positive feedback between mTOR and ROS [60]. As mTOR has been implicated in EMT [61, 62], it is a possibility that some of the changes induced by MMP-3-induced ROS could be associated with the mTOR pathway. This possibility is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example NAC has been shown to inhibit mammalian target of rapamycin (mTOR; [59]), possibly by decreasing ROS and consequently inhibiting the positive feedback between mTOR and ROS [60]. As mTOR has been implicated in EMT [61, 62], it is a possibility that some of the changes induced by MMP-3-induced ROS could be associated with the mTOR pathway. This possibility is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The FAM83D/KID interaction occurs independently of the FAM83D DUF1669, relying on the C-terminus of FAM83D, which has no significant similarity with other FAM83 proteins [77]. FAM83D also interacts with F-box/WD repeat-containing protein 7 (FBXW7) resulting in the down-regulation of FBXW7, a suppressor of c-Myc, mTOR, and C-Jun expression [79]. Thus, elevated expression of FAM83D increases the expression of these downstream oncogenes, which likely contributes to its ability to drive transformation.…”
Section: Other Fam83 Proteinsmentioning
confidence: 99%
“…Emerging evidence has suggested that FBW7 could be regulated by several other factors such as NF-κB1 [198], FAM83D (family with sequence similarity 83, member D) [199]. For example, Huang et al found that NF-κB1 inhibited FBW7 expression and subsequently suppressed its target c-Myc protein degradation [198].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang et al found that NF-κB1 inhibited FBW7 expression and subsequently suppressed its target c-Myc protein degradation [198]. Wang et al reported that FAM83D promoted cell proliferation and migration as well as invasion through downregulation of FBW7 and upregulation of FBW7 target mTOR [199]. Another study showed that SREBP2 regulated miR-182 targeting FBW7, leading to a feedback pathway to regulate SREBP transcriptional activity [200, 201].…”
Section: Introductionmentioning
confidence: 99%